Autobiographical Narrative and the Use of Metaphor: Rilke's Techniques in Die Aufzeichnungen des Malte Laurids Brigge - Lorna Martens (Studies in 20th & 21st Century Literature, 1985)
How can first-person narrative establish a truth claim? Autobiographical narrators have traditionally used visual metaphors in order to reinforce the authority of their discourse. But these metaphors have also been appropriated into the vocabulary of inauthenticity. The specular metaphor, the notion of the self-portrait, and the descriptive language that the self-portrait entails have been seen to introduce the presence of the other into the self-presentation and thereby to undermine the author's claim to privileged insight into himself. In The Notebooks of Malte Laurids Brigge, Rilke,writing in an age when an interest in psychological narration almost automatically doomed first-person narrators to unreliability, uses the mirror metaphor both as a theme and as a formal technique to persuade us of the validity of his narrator's perceptions. Rilke redefines mirroring: understood as a metaphor for artistic creation, it implies rendering visible what normally goes unperceived, while as a technique mirroring calls into play a dialectical interchange between the subject and vehicle of metaphor. In Malte's notebooks, Rilke creates a new model for autobiographical narrative, where Malte himself figures as the "absent" subject of his book or the "unnamed" subject of metaphor. Malte gains in authority as a first-person narrator by turning from self-deception to oblique self-presentation, and from referential to figurative language.
Keywords: first-person narrative; truth; Autobiographical; visual metaphors; self-portrait; self-presentation; The Notebooks of Malte Laurids Brigge; Rilke; psychological narration; unreliability; narrator' s perceptions; mirroring; unperceived; unnamed; absent; authority; first-person narrator; self-deception; figurative language